Internal communication and its relation on organizational commitment in a mass consumption company in peruvian northeast - Saldaña Díaz, Eduardo Iván (2023)
In this article, the main objective was to determine the relationship between internal communication and organizational commitment in the collaborators of a mass consumption company in northeastern Peru; 135 employees of the company participated in this study, to whom a survey was applied as a data collection instrument, the Internal Communication and Organizational Commitment Scales were used, these instruments were subjected to Cronbach's Alpha reliability analysis, to both instruments were obtained as results coefficients that demonstrate reliability (0.906 and 0.769); It should be noted that this study used a methodology for basic research, with a quantitative approach, descriptive-correlational level, with a cross-sectional non-experimental research design. After processing the data, a p-value = 0.000 was determined, which indicates that there is a significant relationship between internal communication and organizational commitment; and a Rho Spearman = 0.586, which indicates that the relationship is considerable positive between the variables studied, in this study it was concluded that, when making efforts to improve internal communication, this action will proportionally influence organizational commitment of collaborators.